Additive Layer Manufacturing using Metal Deposition - Patrice Peyre (Metals, 2020)
Among the additive layer manufacturing techniques for metals, those involving metal deposition, including laser cladding/Direct Energy Deposition (DED, with powder feeding) or Wire and Arc Additive Manufacturing (WAAM, with wire feeding), exhibit several attractive features [...]